Методологія профілактики пошкоджень верхнього гортанного нерва під час операцій на щитоподібній залозі - Шідловський, В. О.; Шідловський, О. В.; Сельський, О. Р.; Саноцька, М. В.; Кузик, Д. С. (Clinical Endocrinology and Endocrine Surgery, 2009)
100 patients with local pathology of thyroid gland were examined. The technique of intraoperative verification of exterior branch of superior laryngeal nerve, the diagnostics and prophylaxis of its damages were developed.